PENGARUH PEMBERDAYAAN, MOTIVASI DAN LINGKUNGAN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN - Purnami, Ni Made Ita; Utama, I Wayan Mudiartha (E-Jurnal Manajemen; Vol 8 No 9 (2019)DO - 10.24843/EJMUNUD.2019.v08.i09.p13, 2019)
The purpose of this study is to find out the effect of empowerment, motivation and work environment on employee work productivity. This research was conducted at Legong Keraton Beach Hotel. The number of respondents studied was 41 employees, using saturated samples. Data collection is done through interviews and questionnaires. The analysis technique used is multiple linear regression. The findings in this study were that empowerment, motivation and work environment had a positive and significant effect on employee work productivity. Legong Keraton Beach Hotel is expected to pay more attention to employees, provide opportunities for employees to make decisions, provide support and motivation, provide salaries according to the workload of employees, maintain cleanliness of the environment and maintain good relationships within the company so that it will affect work productivity to achieve goals effectively and efficient. Keywords: empowerment, motivation, work environment, work productivity of employees